168k views
0 votes
B.
f(x) = -1x - 4; Find f(-3)

User Brad Werth
by
4.5k points

1 Answer

5 votes

Answer:

f(-3) = -1

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Functions
  • Function Notation

Explanation:

Step 1: Define

Identify

f(x) = -1x - 4

Step 2: Evaluate

  1. Substitute in x [Function f(x)]: f(-3) = -1(-3) - 4
  2. Multiply: f(-3) = 3 - 4
  3. Subtract: f(-3) = -1
User Alex Coventry
by
5.0k points